Technological opportunities and challenges for Singapore logistics firm (sea perspective) - Tan, Bronessa Yan Ning (Nanyang Technological University, 2021)
The study identifies the technological solutions available in the maritime industry, and the opportunities and challenges faced by maritime logistics firms in Singapore in their journey to digitalise. The study then seeks to encourage technological adoptions by these firms, through a series of recommendations, such that the benefit of solutions can continue to be harnessed and enjoyed, despite certain constraints and limitations. Technological advancement is changing every aspect of the maritime landscape, and how businesses operate. Mega vessels, accentuated cargo volume peaks and increased complexity of shipping operations call for technological solutions to be employed, such that firms can continue to deliver high service levels, while staying ahead of the curve. Especially for Singapore, the maritime industry plays a key role in our economic activities and job creation opportunities, contributing 7% GDP, and employing more than 170,000 of the workforce. As such, defining a clear digital strategy that is integrated with business strategy will be critical. Digital Business Strategy will be the new and essential way firms operate, as these strategies leverage on digital resources to create higher business value and sustainable competitive advantage. The literature review discusses how the concept of industry 4.0 is changing expectations and revolutionising the maritime industry. For that reason, the Singapore authorities have launched various initiatives to aid the industry’s technological adoption effort, including the Sea Transport Industry Digital Plan (IDP) and Maritime Digitalisation Playbook (MDP). The literature review has identified that opportunities such as the call for efficiency and sustainability were giving rise to enabling technological solutions including drone deliveries and Additive Manufacturing (AM), but wider adoption scale by the industry has been hindered due to factors like digital trust and digital immaturity. Given that the industry has been conservative in terms of technological adoption, many proven technological solutions used by other digitally advanced industries are available to be implemented. However, the industry remains relatively slow in adopting and utilising these solutions. Therefore, we have conducted interviews with various industry representatives from both the maritime and technological sectors to gather their perspectives on this subject matter, and learn how they could overcome these challenges, to become successful enterprises and start-ups today. The findings showed commonality across the firms, despite the difference in size and nature, and a series of recommendations are taken from their experience to encourage Singapore’s maritime logistics firms to digitalise.